The mechanical regulation of skeletal development : identification and characterisation of mechanosensitive genes that contribute to tissue differentiation in bone and joint development - Rolfe, Rebecca A. (Trinity College (Dublin, Ireland). Department of Zoology, 2015)
Mechanical stimulation has been implicated as an important regulator for the development of the skeleton. Decreased in utero foetal movement results in skeletal abnormalities including joint fusions and thin hypo-mineralised bones. Animal models that develop in the absence of mechanical stimulation show abnormal initiation and/or progression of ossification in long bones, loss of definition of tissue territories in the joint region and altered rudiment morphology (Kahn et al., 2009; Nowlan et al., 2010a; Roddy et al., 2011b). The skeletal system is a complex structure, and while we know much about the molecular mechanisms that guide the differentiation of progenitor cells into its individual elements; we know very little of the molecular mechanisms that sense and respond to mechanical stimulation to co-ordinate its correct development. The objective of this thesis was to uncover the molecular mechanisms underlying the response of developing skeletal cells to mechanical stimulation.
Keywords: Zoology, Ph.D.; Ph.D. Trinity College Dublin